Onium salt compound, photoacid generator, photoresist composition, and pattern forming method
By using onium salt compounds as photoacid generators in photoresist and combining with photoresist, the problem of the diffusion length of the photoacid generator in the photoresist is solved, which significantly improves the LWR performance of the photolithographic pattern, and achieves the formation of high-resolution patterns, while reducing environmental impact.
Patent Information
- Application Number
- CN202411908274.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In high-resolution photolithography technology, the diffusion length of the photoacid generator in the photoresist is close to the size of the formed pattern, making it difficult to form a high-resolution pattern, and the line width roughness is greatly affected by the acid diffusion.
It is provided as a photoacid generator, combined with a photoresist, to control the acid diffusion length through its acid generation ability under light and the action of large sterically resistive groups, and improve the linewidth roughness (LWR) performance of the photolithographic pattern.
The LWR performance of the resist composition is significantly improved, and the lithographic pattern with high resolution can be formed, and the acetal and ester-based structures of onium salt compounds are easily decomposed, reducing the impact on the environment.
Smart Images

Figure CN119751407A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of photoresists, and in particular to an onium salt compound, a photoacid generator, a photoresist composition and a pattern forming method. Background Art
[0002] Immersion lithography is an advanced lithography technology that increases the numerical aperture (NA) of the system by filling a certain liquid between the projection objective and the silicon wafer, thereby improving resolution and expanding the lithography process node. This technology mainly uses an ArF light source with a wavelength of 193nm to fill the liquid (usually ultrapure water with a refractive index of 1.44) between the lower surface of the last lens of the projection objective and the silicon wafer to achieve a higher numerical aperture and exposure resolution.
[0003] However, with the continuous miniaturization of photolithography, the diffusion length of the photoacid generator in the photoresist is getting closer and closer to the size of the pattern formed, so it is increasingly difficult to form a high-resolution pattern on the photoresist. In addition, the higher the resolution, the line width roughness (LWR) of the photoresist pattern is also greatly affected by acid diffusion. The uneven distribution of the photoacid generator (PAG) in the resist film will also have an adverse effect on the line width roughness. The structure of the PAG anion has a profound effect on the diffusion characteristics of the photogenerated acid by affecting the interaction between the photoacid generator and other photoresist components. Therefore, it is necessary to design a PAG anion structure with excellent structure to further meet the requirements of low LWR and excellent lithography performance. Summary of the invention
[0004] The purpose of the present invention is to solve the above problems and provide an onium salt compound, a photoacid generator, a photoresist composition and a pattern forming method, which can significantly improve the LWR performance of the resist composition, thereby forming a pattern with high resolution.
[0005] The first aspect of the present invention provides an onium salt compound, the general structural formula of which is:
[0006]
[0007] Wherein, R1, R2, R3, and R4 are each independently a heteroatom-substituted or unsubstituted C1 to C 20 One or more combinations of aliphatic chain hydrocarbon groups or cycloalkane groups;
[0008] Cation Z + including sulfonium cations;
[0009] Furthermore, R1, R2, R3, and R4 each independently comprise one or more combinations of methyl, cyclopentyl, and cyclohexyl;
[0010] Preferably, R1, R2, R3, and R4 are each independently cyclopentyl or cyclohexyl, or a combination of both;
[0011] It is further preferred that R1, R2, R3, and R4 are all cyclohexyl;
[0012] Furthermore, the onium salt compound comprises one or a combination of the following compounds:
[0013]
[0014] The preferred onium salt compounds are:
[0015]
[0016] The second aspect of the present invention provides a photoacid generator comprising the onium salt compound provided by the first aspect of the present invention.
[0017] The third aspect of the present invention provides a resist composition, comprising the photoacid generator provided by the second aspect of the present invention, a quencher, a base resin, a fluorine-containing resin and a solvent;
[0018] The quencher comprises one or more combinations of ionic organic matter or amine compounds, and the base resin is a polyacrylate derivative;
[0019] Furthermore, the cation of the ionic quencher is one or more combinations of the following structures:
[0020]
[0021]
[0022] The preferred cation of the ionic quencher is:
[0023]
[0024] The anion of the ionic quencher is one or more combinations of the following structures:
[0025]
[0026] The preferred anion of the ionic quencher is:
[0027]
[0028] The further preferred anion of the ionic quencher is:
[0029]
[0030] The amine-type quencher is one or more combinations of the following structures:
[0031]
[0032] The preferred amine quencher is:
[0033]
[0034] The further preferred amine quencher is:
[0035]
[0036] The quencher includes a combination of an ionic quencher and an amine quencher, and a preferred quencher combination is a combination of triphenylsulfonyl camphor sulfonate and tri-n-pentylamine, triphenylsulfonyl camphor sulfonate and tri-n-octylamine, and a further preferred quencher combination is a combination of triphenylsulfonyl camphor sulfonate and tri-n-pentylamine;
[0037] Furthermore, the base resin is a ternary copolymer resin, and its repeating unit is:
[0038]
[0039] Where R A Each independently represents a hydrogen atom or a methyl group; X1 and X2 each independently represent an acid-labile group, and Y is a polar group comprising one or more combinations of cyano, carbonyl, carboxyl, ether bond, ester bond, sulfonate bond, carbonate bond, lactone ring, sultone ring, and carboxylic anhydride;
[0040] Furthermore, the acid-labile groups X1 and X2 each independently comprise one or more combinations of the following structures:
[0041]
[0042] Preferably, the acid-labile groups X1 and X2 are:
[0043]
[0044] The Y group is one or more combinations of the following structures:
[0045]
[0046] The preferred Y group is:
[0047]
[0048] Furthermore, the photoacid generator (A), quencher (B), base resin (C) and fluorine-containing resin (D) of the resist composition are respectively:
[0049]
[0050] The solvent (E) is a mixed solution of propylene glycol monomethyl ether acetate, γ-butyrolactone and cyclohexanone.
[0051] A fourth aspect of the present invention provides a pattern forming method, comprising the following steps:
[0052] S1, film formation: coating the resist composition described in the third aspect of the present invention on a substrate and curing the resist composition described in the third aspect of the present invention to form a photoresist film.
[0053] S2, immersion exposure: light of a specific wavelength is transmitted through a liquid medium and then irradiated onto a specific area of the photoresist film for exposure.
[0054] S3, Development: The photoresist film is treated with an alkaline aqueous solution.
[0055] Beneficial effects:
[0056] (1) The present invention provides a novel onium salt compound that is completely soluble and uniformly dispersible in an organic solvent. In addition, the acetal and ester structures in the onium salt compound make it easy to decompose itself, thereby minimizing the impact on the environment.
[0057] (2) When the onium salt compound of the present invention is used as a photoacid generator in a resist composition, the uniformity of the composition can be ensured, and its large steric hindrance group can effectively reduce the acid diffusion length and improve the LWR performance of the photolithographic pattern. DETAILED DESCRIPTION
[0058] The embodiments of the present invention will be described in detail below in conjunction with examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. In the examples, specific conditions are not indicated, and are carried out under the conditions of normal conditions or manufacturer recommendations. Reagents used or instruments that do not indicate manufacturers are conventional products that can be purchased and obtained commercially. In addition, unless otherwise specified, "parts" in the examples of the present application represent mass fractions.
[0059] The onium salt compound, photoacid generator, and resist composition of the present invention are described in detail below.
[0060] <Onium Salt Compounds>
[0061] The first aspect of the present invention provides an onium salt compound, the general structural formula of which is as follows:
[0062]
[0063] Wherein, R1, R2, R3, and R4 are each independently a heteroatom-substituted or unsubstituted C1 to C 20 One or more combinations of aliphatic chain hydrocarbon groups or cycloalkane groups; Z + Includes sulfonium cations.
[0064] In the present invention, the onium salt compound can generate acid when exposed to light, and the generated acid can cause a polymer compound such as a matrix resin to undergo a deprotection reaction, thereby changing the solubility of the polymer compound itself. After the matrix resin coated with the onium salt compound is developed, a specific pattern can be generated on the polymer compound such as the matrix resin.
[0065] In the present invention, when the adamantane group in the anion part of the onium salt compound is connected with a group such as a lactone or an acetal and used together, a rigid molecular structure can be formed to restrict its movement. At the same time, the hydrogen bond interaction between these sterically hindered groups and the photoacid can further effectively control the length of acid diffusion and improve the LWR performance of the photolithographic pattern. In addition, the ester group and the acetal are easily decomposed, so that after use, the onium salt compound can be degraded, which can minimize its impact on the environment.
[0066] The R1, R2, R3, and R4 groups in the cyclic acetal portion generally play an auxiliary role in regulating steric hindrance, and they can be independently heteroatom-substituted or unsubstituted C1-C 20 One or more combinations of aliphatic chain hydrocarbon groups or cycloalkane groups.
[0067] C1~C 20 The aliphatic hydrocarbon group may be one or more combinations of straight chain, branched chain or cyclic structure, and examples thereof include methyl, isopropyl, sec-butyl, tert-butyl, tert-pentyl, n-pentyl, n-hexyl, n-octyl, n-nonyl, cyclopentyl, cyclohexyl, 2-ethylhexyl, cyclopentylmethyl, cyclopentylethyl, cyclopentylbutyl, cyclohexylmethyl, cyclohexylethyl, cyclohexylbutyl, norbornyl, adamantyl, adamantylmethyl and other alkyl groups. Compared with straight chain aliphatic hydrocarbon groups with the same number of carbon atoms, branched aliphatic hydrocarbon groups or cyclic aliphatic hydrocarbon groups have greater steric hindrance, thereby reducing the acid diffusion length of onium salt compounds, which is conducive to better control of the acid diffusion length. Therefore, one or more combinations of branched aliphatic hydrocarbon groups and cyclic aliphatic hydrocarbon groups are preferred. More specifically, one or a combination of aliphatic hydrocarbon groups such as cyclopentyl and cyclohexyl groups may be used. It is further preferred that R1, R2, R3 and R4 are all cyclohexyl groups. In addition, C1~C 20 Some hydrogen atoms in the aliphatic hydrocarbon group may also be replaced by groups containing heteroatoms such as oxygen atoms, sulfur atoms, nitrogen atoms, halogen atoms, etc., or groups containing heteroatoms such as oxygen atoms, sulfur atoms, nitrogen atoms, etc. may exist between carbon atoms to form C1~C 20Aliphatic hydrocarbon group, containing heteroatoms C1~C 20 The aliphatic hydrocarbon group may contain one or more combinations of hydroxyl groups, cyano groups, carbonyl groups, ether bonds, thioether bonds, ester bonds, sulfonate bonds, carbonate bonds, carbamate bonds, lactone rings, and the like.
[0068] Due to the presence of large steric hindrance groups, its solubility is generally poor, the stacking degree is high, and it is difficult to completely dissolve and evenly disperse in organic solvents. Therefore, in the present invention, the adamantane group and the ester group with large steric hindrance will interact with SO3 - connection, so that the onium salt compound can be completely soluble and uniformly dispersed in the organic solvent.
[0069] For ease of understanding, as an example, the anion of the present invention is given the following specific structural formula as an illustration:
[0070]
[0071] Preferably:
[0072]
[0073] More preferably:
[0074]
[0075] The cation of the present invention is an unsubstituted or substituted derivative of triphenylsulfonium salt, and the substituent includes one or more combinations of alkyl, alkoxy, hydroxyl, and fluorine-containing groups, thereby ensuring that the cationic part can maintain a balance between solubility and photosensitivity. For ease of understanding, as an example, the specific structural formula of the cationic structure is given:
[0076]
[0077] Preferably:
[0078]
[0079] In the present invention, the onium salt compound comprises one or a combination of the following compounds:
[0080]
[0081] The preferred onium salt compounds are:
[0082]
[0083] Of course, the specific embodiment of the present invention also provides a specific preparation method of the above-mentioned onium salt compound, and its synthesis route is as follows:
[0084]
[0085] If one wants to obtain onium salt compounds with different substituents, one only needs to change the substituents based on the raw materials. Therefore, the present invention will not describe in detail the synthesis method of each onium salt compound.
[0086] <Photoacid generator>
[0087] The second aspect of the present invention provides a photoacid generator, the components of which include the onium salt compound described in the first aspect of the present invention.
[0088] The photoacid generator can generate acid under light exposure, thereby denaturing the matrix resin and changing the solubility of the matrix resin. The photoacid generator of the present invention has a short acid diffusion length under light exposure, and can effectively control the acid diffusion length, thereby improving the LWR performance of the photolithographic pattern and forming a pattern with higher resolution.
[0089] <Resist Composition>
[0090] The third aspect of the present invention provides a resist composition, the components of which include the photoacid generator described in the second aspect of the present invention, a quencher, a base resin, a fluorine-containing resin and a solvent.
[0091] Quencher
[0092] The anti-etching composition of the present invention comprises a quencher, and the quencher comprises one or more combinations of ionic organic matter or amine compounds.
[0093] In the resist composition, the quencher can capture the excess acid compounds generated by the PAG to prevent other regions of the matrix resin from being denatured. Therefore, the quencher is generally an ionic organic substance with a weaker acidity.
[0094] The cation of the ionic quencher is one or more combinations of the following structures:
[0095]
[0096] The preferred cation of the ionic quencher is:
[0097]
[0098] The anion of the ionic quencher is one or more combinations of the following structures:
[0099]
[0100] The preferred anion of the ionic quencher is:
[0101]
[0102] The further preferred anion of the ionic quencher is:
[0103]
[0104] Any of the above cations and any of the anions are combined to form a complete quencher. The ionic quencher acts as a quencher in the unexposed area, and neutralizes with the acid generated by itself in the exposed area and loses the quencher function in the exposed area, which can further improve the contrast between the exposed area and the unexposed area.
[0105] In the present invention, the amine-type quencher is one or more combinations comprising the following structures:
[0106]
[0107] The preferred amine quencher is:
[0108]
[0109] The further preferred amine quencher is:
[0110]
[0111] In the present invention, the ionic quencher can be used in combination with the amine quencher, so as to further improve the contrast between the exposed area and the unexposed area and improve the LWR. Preferably, triphenylsulfide camphor sulfonate and tri-n-pentylamine are used as a set of quenchers, or triphenylsulfide camphor sulfonate and tri-n-octylamine are used as a set of quenchers, and more preferably, triphenylsulfide camphor sulfonate and tri-n-pentylamine are used as a set of quenchers.
[0112] In the present invention, the acidity of the quencher is required to be lower than that of the photoacid, so the quencher can capture the excess acid compounds generated by the PAG to prevent other areas of the matrix resin that are not exposed to light from being denatured.
[0113] Base resin
[0114] In the present invention, the base resin is a polyacrylate derivative, and the base resin of the polyacrylate derivative can allow light with a wavelength of 193nm and below to pass through, thereby ensuring that other components in the composition can be irradiated by the light.
[0115] In the present invention, the base resin is a ternary copolymer resin, and its repeating unit is:
[0116]
[0117] Where R AEach is independently a hydrogen atom or a methyl group; X1 and X2 are each independently an acid-labile group, and Y is a polar group comprising one or more combinations of cyano, carbonyl, carboxyl, ether bond, ester bond, sulfonate bond, carbonate bond, lactone ring, sultone ring, and carboxylic anhydride.
[0118] In the present invention, the acid-labile groups X1 and X2 can react with an acid, thereby changing the solubility of the matrix resin, so that a pre-designed photolithographic pattern can be photoetched on the matrix resin. Specifically, the X1 and X2 groups each independently include one or more combinations of the following structures:
[0119]
[0120] Preferably, the acid-labile groups X1 and X2 are:
[0121]
[0122] The Y group is one or more combinations of the following structures:
[0123]
[0124] The preferred Y group is:
[0125]
[0126] The base resin is generally formed by polymerization of acrylate derivatives. For example, when the X1 and X2 groups satisfy the above structural formula, the synthetic monomer corresponding to the repeating unit is generally:
[0127]
[0128] Preferably:
[0129]
[0130] Similarly, when the Y group satisfies the above structural formula, the synthetic monomer corresponding to its repeating unit is generally:
[0131]
[0132] Preferably:
[0133]
[0134] In addition, the weight average molecular weight (Mw) of the matrix resin is generally controlled within the range of 1000 to 10000 g / mol, preferably 3000 to 8000 g / mol. By controlling Mw within this range, the matrix resin has sufficient etching resistance and also avoids any resolution reduction problem caused by not being able to establish a dissolution rate difference before and after exposure.
[0135] Mw can be measured by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as solvent against a polystyrene standard. Specifically, a GPC column manufactured by Agilent can be used, and the analysis conditions are a flow rate of 1.0 mL / min, tetrahydrofuran as the elution solvent, and a column temperature of 40°C, and the measurement is performed by gel permeation chromatography (GPC) using monodisperse polystyrene as the standard.
[0136] In addition, as the pattern rules become finer and finer, the influence of molecular weight and dispersity becomes stronger and stronger. Therefore, in order to formulate a resist composition suitable for high-resolution pattern formation, the polymer should preferably have a narrow dispersity of 1.0 to 2.0 (dispersity is expressed by Mw / Mn, Mn is the number average molecular weight). Narrower dispersity is conducive to forming a more precise lithographic pattern on the matrix resin. If the polymer has a broad molecular weight distribution or dispersity, which indicates that there are polymer parts with lower and higher molecular weights, there is a possibility that foreign matter is left on the pattern or the pattern profile is degraded.
[0137] When the base resin polymer contains the above three repeating units, the molar fraction of each unit preferably falls within the following range (mol%), but is not limited thereto: (I) preferably 5-40 mol%, more preferably 10-30 mol% of at least one repeating unit having formula (a), (II) preferably 20-60 mol%, more preferably 30-50 mol% of at least one repeating unit having formula (b), (III) preferably 30-70 mol%, more preferably 40-60 mol% of at least one repeating unit having formula (c). The unit of formula (a) is a repeating unit with X1, the unit of formula (b) is a unit with X2 group, and the unit of formula (c) is a unit with Y group.
[0138] Fluorine-containing resin
[0139] In the resist composition of the present invention, the fluorine-containing resin has a tendency to separate on the resist surface after the resist composition is spin-coated to form a film. Due to the presence of the fluorine-containing resin, water and water-soluble components are not easy to seep out from the resist film formed by the resist composition. Therefore, the resist composition containing the fluorine-containing resin can play a good role in protecting the exposure lens of the photolithography machine. In addition, the fluorine-containing resin also needs to contain a specific acid dissociable group, so that its solubility in the alkaline development after exposure and PEB will increase, so that it can be removed and reduce defects after development.
[0140] Specifically, the repeating unit of the fluorine-containing resin is as follows:
[0141]
[0142] Wherein R comprises one or more combinations of hydrogen atoms, fluorine atoms, methyl groups or trifluoromethyl groups; L G is an acid-labile group, and for details, reference may be made to the above-mentioned contents regarding X1 and X2 of the present invention, R f5 It is a fluorinated hydrocarbon having 1 to 30 carbon atoms.
[0143] L G Preferably:
[0144]
[0145] R f5 Including but not limited to:
[0146]
[0147] Preferably:
[0148]
[0149] Solvents
[0150] In the resist composition, the organic solvent can dissolve other components and ensure that the components of the resist composition are uniform, so that a photolithographic pattern with higher resolution can be formed when applied. The organic solvent is not particularly limited as long as it can dissolve other components. For example, the organic solvent can be a ketone solvent such as cyclohexanone, methyl-2-n-pentyl ketone; an alcohol solvent such as 3-methoxybutanol, 3-methyl-3-methoxybutanol, 1-methoxy-2-propanol; an ether solvent such as propylene glycol monomethyl ether, ethylene glycol monomethyl ether, propylene glycol monoethyl ether, ethylene glycol monoethyl ether, propylene glycol dimethyl ether; an ester solvent such as propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, ethyl lactate; a lactone solvent such as γ-butyrolactone.
[0151] In the present invention, the organic solvent can be any one or more mixed solvents. To ensure good solubility, the generally preferred organic solvent is one or more combinations of propylene glycol monomethyl ether acetate, cyclohexanone, and γ-butyrolactone, and the further preferred organic solvent is a mixed solvent of propylene glycol monomethyl ether acetate, cyclohexanone, and γ-butyrolactone.
[0152] In the present invention, specifically, the photoacid generator (A), quencher (B), base resin (C) and fluorine-containing resin (D) of the resist composition are respectively:
[0153]
[0154] The solvent (E) is a mixed solution of propylene glycol monomethyl ether acetate, γ-butyrolactone and cyclohexanone.
[0155] The above-mentioned resist composition is the most preferred combination, has good solution uniformity, can reduce the acid diffusion length, and improve the LWR performance of the photolithography pattern.
[0156] <Pattern Formation Method>
[0157] The fourth aspect of the present invention provides a pattern forming method. When the photolithography pattern is formed using the resist composition of the third aspect of the present invention, the following steps are generally performed:
[0158] S1, film formation: coating the resist composition described in the third aspect of the present invention on a substrate and curing the resist composition described in the third aspect of the present invention to form a photoresist film.
[0159] In this step, the resist composition is generally coated on the substrate by a spin coater, and then the resist composition is cured by drying to form a photoresist film.
[0160] S2, immersion exposure: light of a specific wavelength is transmitted through a liquid medium and then irradiated onto a specific area of the photoresist film for exposure.
[0161] In this step, light is generally passed through a mask so that the light is irradiated on a specific area of the photoresist film. The liquid medium is generally water. The light first passes through the mask, then through the liquid medium, and then irradiates the surface of the photoresist film for exposure.
[0162] S3, Development: The photoresist film is treated with an alkaline aqueous solution.
[0163] In this step, the photoresist film in the exposed area can be removed using an alkaline aqueous solution, thereby forming a high-resolution pattern on the surface of the photoresist film.
[0164] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0165] Preparation Example 1
[0166] This embodiment provides an onium salt compound PAG1, and its specific synthesis route is as follows:
[0167] (1) Synthetic intermediate A:
[0168] Carbonyldiimidazole (CDI, 16.2 g) was added to a 500 mL tetrahydrofuran solution of 2-bromo-2,2-difluoroacetic acid (17.49 g), and the mixture was stirred at room temperature for 2 hours. The mixture was then heated to 70°C, and the intermediate 5-hydroxy-2-adamantanone (16.22 g) was added to the reaction, and the reaction was carried out at 70°C for 16 hours under nitrogen protection.
[0169] After the reaction was completed, the solvent was removed under reduced pressure, and the residual oil was dissolved in 200 mL of dichloromethane. The dichloromethane containing the oil was then washed with 200 mL of NH4Cl solution twice, and then washed once with 200 mL of water. After the washing was completed, the dichloromethane solution containing the oil after washing was dried with MgSO4, and the dichloromethane was removed under reduced pressure to obtain 21.33 g of intermediate A. The specific reaction formula is as follows:
[0170]
[0171] (2) Synthesis of intermediate C:
[0172] To a solution of A (21.33 g) in 500 mL of tetrahydrofuran was added p-toluenesulfonic acid (TsOH, 0.875 g), and the mixture was stirred at room temperature for 2 hours. The mixture was then heated to 70°C, and B (22.08 g) was added to the reaction, and the reaction was carried out at 50°C for 16 hours under nitrogen protection.
[0173] After the reaction was completed, the solvent was removed under reduced pressure, and the residual oil was dissolved in 200 mL of dichloromethane. The dichloromethane containing the oil was then washed with 200 mL of NH4Cl solution twice, and then washed once with 200 mL of water. After the washing was completed, the dichloromethane solution containing the oil after washing was dried with MgSO4, and the dichloromethane was removed under reduced pressure to obtain 31.98 g of intermediate C. The specific reaction formula is as follows:
[0174]
[0175] (3) Dissolve intermediate C (31.98 g) in 200 mL of acetonitrile, and dissolve sodium dithionite (1.74 g) and sodium bisulfite (10 g) in 200 mL of deionized water. Add the stirred acetonitrile solution containing intermediate C to the aqueous solution to form a mixed solution, stir at 70°C for 16 hours, and 19F-NMR detects whether the reaction is complete. After the reaction is complete, 100mL of water, 50mg of Na2WO4·2H2O, and 14.5g of H2O2 (30wt% aqueous solution) are added to the reaction system, and the reaction is stirred at room temperature for 16 hours. After the reaction is completed, the organic phase is evaporated on a rotary evaporator, and then the residual solid is dissolved in 100L of acetone, and then the solution is slowly poured into 2L of methyl tert-butyl ether. The waxy product is separated by decantation to remove the solvent, and the obtained waxy product is further dried under reduced pressure to obtain 22.52g of the crude product of intermediate D, which is directly used in the next step. The reaction formula is as follows:
[0176]
[0177] (4) Synthesis of PAG1: Add intermediate D (22.52 g) and triphenylsulfide bromide (TPSBr, 11.63 g) to a mixed solution of 200 mL of dichloromethane and 200 mL of deionized water, and stir the reaction at room temperature overnight. After the reaction is completed, separate the aqueous phase and the organic phase, and then wash the organic phase 5 times with 200 L of deionized water. Pour the concentrated and separated organic phase into methyl tert-butyl ether to generate 22.16 g of the photoacid generator PAG1, and the reaction formula is as follows:
[0178]
[0179] The purity of the PAG1 sample was checked by HPLC-MS. The cation purity was 99.8% by UV at 220 nm, 99.6% by cation chromatography mass spectrometry, and 99.7% by anion chromatography mass spectrometry. LCMS: cation 263; anion 703.
[0180] Preparation Example 2
[0181] According to the above-mentioned synthesis method, Example 2 provides an onium salt compound named PAG2, and the specific structure is as follows:
[0182]
[0183] Example
[0184] The present invention provides a resist composition with different components to explore the effect of a photoacid generator on the performance of the resist composition. The components of the resist composition of the present application are specifically described as follows:
[0185] A represents a photoacid generator, and A1 to A2 correspond to PAG1 to PAG2 in sequence, wherein A3 to A5 correspond to PAG3 to PAG5 in sequence. The specific structural formulas are as follows:
[0186]
[0187] B represents a quencher, and B1 is triphenylsulfide salicylate, B2 is triphenylsulfide camphorsulfonate, B3 is tri-n-pentylamine, and B4 is tri-n-octylamine.
[0188] C represents the base resin, 13 The results of C-NMR analysis showed that the molar ratio of a, b, and c was 43:5:52. Its repeating unit is:
[0189]
[0190] D represents fluorine-containing resin, 13 The results of C-NMR analysis showed that the molar ratio of d to e was 81:19. Its repeating unit is:
[0191]
[0192] E represents an organic solvent, and E1 represents propylene glycol monomethyl ether acetate, E2 represents γ-butyrolactone, and E3 represents cyclohexanone.
[0193] The specific components and proportions of various resist compositions are shown in the following table:
[0194] Table 1 Components and ratios of the resist compositions in the examples and comparative examples
[0195]
[0196] The resist compositions of Examples 1 to 6 and Comparative Examples 1 to 3 were subjected to performance tests of sensitivity and LWR according to the following evaluation methods.
[0197] A base antireflection film-forming composition (trade name: "ARC66") was applied to the surface of a 12-inch silicon wafer using a spin coater ("CLEANTRACK ACT12" manufactured by Tokyo Electron Co., Ltd.) to form a base antireflection film having an average thickness of 105 nm.
[0198] The resist compositions in all embodiments and all comparative examples were respectively coated on the surface of a 12-inch silicon wafer using a spin coater, and then baked at 120°C for 60 seconds, and then cooled at 23°C for 30 seconds to form a resist film with an average thickness of 85nm. Next, an ArF excimer laser immersion exposure system (model "TWINSCANXT-1980Di", produced by ASML Co.) was used to expose a mask pattern with a line of 38nm and a spacing of 76nm under optical conditions. The exposure parameters were: NA of 1.35, dipole illumination (o-0.98 / 0.90). After exposure, PEB was performed at 85°C for 60 seconds. Thereafter, an aqueous solution of tetramethylammonium hydroxide (TMAH) with a mass fraction of 2.38% was used to perform alkaline development on the resist film. After development, it was washed with water and then dried to form a positive resist pattern.
[0199] (1) Sensitivity test
[0200] The exposure dose when a 38 nm line and a 76 nm pitch exposure pattern are formed on the resist composition after the ArF exposure is defined as the optimal exposure dose (i.e., Eop), and is used as the sensitivity Eop (unit: mJ / cm 2 ).
[0201] (2) LWR test
[0202] The line width of the 1:1 Line / Space pattern at 36nm was measured under SEM (scanning electron microscope) to determine the line width variation (measure 30 points and calculate the 3σ value), which is recorded as LWR. The smaller the LWR value, the smaller the fluctuation of the line pattern and the better the profile.
[0203] The above measurement results are shown in the following table:
[0204] Table 2 Performance test results of embodiments and comparative examples
[0205]
[0206]
[0207] As can be seen from Table 2, the resist composition of the present invention, because it contains an onium salt-based PAG, is particularly suitable for ArF immersion lithography because it forms a pattern with high resolution, high sensitivity and low LWR.
[0208] It should be noted that, according to the explanation and elaboration of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some equivalent modifications and changes to the present invention should also be within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the invention.
Claims
1. An onium salt compound, characterized in that: Its general structural formula is: Wherein, R1, R2, R3, and R4 are each independently a heteroatom-substituted or unsubstituted C1 to C 20 One or more combinations of aliphatic chain hydrocarbon groups or cycloalkane groups; Cation Z + Includes sulfonium cations.
2. The onium salt compound according to claim 1, characterized in that The R1, R2, R3, and R4 each independently contain one or more combinations of methyl, cyclopentyl, and cyclohexyl. Preferably, the R1, R2, R3, and R4 each independently contain one or more combinations of cyclopentyl and cyclohexyl. More preferably, the R1, R2, R3, and R4 are all cyclohexyl.
3. The onium salt compound according to claim 2, characterized in that: The onium salt compound comprises one or a combination of the following compounds: The preferred onium salt compound is:
4. A photoacid generator, characterized in that: Contains the onium salt compound according to any one of claims 1 to 3.
5. A resist composition, characterized in that It comprises the photoacid generator as claimed in claim 4, a quencher, a matrix resin, a fluorine-containing resin and a solvent; the quencher comprises one or more combinations of ionic organic matter or amine compounds, and the matrix resin is a polyacrylate derivative.
6. The resist composition according to claim 5, characterized in that The cation of the ionic quencher is one or more combinations of the following structures: The preferred cation of the ionic quencher is: The anion of the ionic quencher is one or more combinations of the following structures: The preferred anion of the ionic quencher is: The further preferred anion of the ionic quencher is: The amine-type quencher is one or more combinations of the following structures: The preferred amine quencher is: The further preferred amine quencher is: The quencher includes a combination of an ionic quencher and an amine quencher. The preferred quencher combination is a combination of triphenylsulfide camphor sulfonate and tri-n-pentylamine, triphenylsulfide camphor sulfonate and tri-n-octylamine, and a further preferred quencher combination is a combination of triphenylsulfide camphor sulfonate and tri-n-pentylamine.
7. The resist composition according to claim 5, characterized in that The base resin is a ternary copolymer resin, and its repeating unit is: Where R A Each is independently a hydrogen atom or a methyl group; X1 and X2 are each independently an acid-labile group, and Y is a polar group comprising one or more combinations of cyano, carbonyl, carboxyl, ether bond, ester bond, sulfonate bond, carbonate bond, lactone ring, sultone ring, and carboxylic anhydride.
8. The resist composition according to claim 7, characterized in that The acid-labile groups X1 and X2 each independently comprise one or more combinations of the following structures: Preferably, the acid-labile groups X1 and X2 are: The Y group is one or more combinations of the following structures: The preferred Y group is:
9. The resist composition according to any one of claims 5 to 8, characterized in that The photoacid generator (A), quencher (B), base resin (C) and fluorine-containing resin (D) of the resist composition are respectively: The solvent (E) is a mixed solution of propylene glycol monomethyl ether acetate, γ-butyrolactone and cyclohexanone.
10. A pattern forming method, characterized in that: The following steps are involved: S1, film formation: coating the resist composition according to any one of claims 5 to 9 on a substrate and curing the resist composition according to any one of claims 5 to 9 to form a photoresist film. S2, immersion exposure: light of a specific wavelength is transmitted through a liquid medium and then irradiated onto a specific area of the photoresist film for exposure. S3, Development: The photoresist film is treated with an alkaline aqueous solution.
Citation Information
Patent Citations
Salt and photoresist composition containing the same
CN101955476A
Resist composition and pattern forming method
CN112782934A
Onium salt, resist composition, and pattern forming method
CN117384130A
Resist composition, and patterning method
JP2023116474A